The Effects of Founders’ Characteristics on Student Spin-Offs Intention: A Gender Analysis - Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez; Noor Azlinna, Azizan (GBMR, 2018)
Purpose: This paper aims to drawing on the Theory of Planned Behavior (TPB), explore the effects of founders’ characteristics on student spin-offs intention (SI) and examines the question of whether the effects are vary by gender. Design/methodology/approach: Data were collected from a sample of 369 students at eleven public universities in Malaysia. Partial least square-structural equation modelling, bootstrap procedure and multi-group analysis were used to analyze the data.